2015
DOI: 10.3390/coatings5020095
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity of Epoxy/Ag-TiO2 Polymer Nanocomposite Coatings against Staphylococcus Aureus and Escherichia Coli

Abstract: Dispersion of functional inorganic nano-fillers like TiO2 within polymer matrix is known to impart excellent photobactericidal activity to the composite. Epoxy resin systems with Ag + ion doped TiO2 can have combination of excellent biocidal characteristics of silver and the photocatalytic properties of TiO2. The inorganic antimicrobial incorporation into an epoxy polymeric matrix was achieved by sonicating laboratory-made nano-scale anatase TiO2 and Ag-TiO2 into the industrial grade epoxy resin. The resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It is worth mentioning that the lower effect of Fe 3 O 4 NPs on biofilm formation may be a result of the chelation mechanisms of iron by biofilm structure. , Antibiofilm activity of copper NPs was reported as higher values of 90.58% for P. aeruginosa PACI02 clinical pathogens . Nanocomposite by 1.5 wt % of Ag-TiO 2 had complete reduction in biofilm of S. aureus and E. coli during 24 h treatment . ZnO NPs demonstrated an antibiofilm property on E. coli O157:H7, methicillin-resistance S. aureus (MRSA), methicillin-sensitive S. aureus (MSSA), and P. aureuginosa PAO1 strains at 1, 5, 5, and 1 mM concentrations .…”
Section: Resultsmentioning
confidence: 97%
“…It is worth mentioning that the lower effect of Fe 3 O 4 NPs on biofilm formation may be a result of the chelation mechanisms of iron by biofilm structure. , Antibiofilm activity of copper NPs was reported as higher values of 90.58% for P. aeruginosa PACI02 clinical pathogens . Nanocomposite by 1.5 wt % of Ag-TiO 2 had complete reduction in biofilm of S. aureus and E. coli during 24 h treatment . ZnO NPs demonstrated an antibiofilm property on E. coli O157:H7, methicillin-resistance S. aureus (MRSA), methicillin-sensitive S. aureus (MSSA), and P. aureuginosa PAO1 strains at 1, 5, 5, and 1 mM concentrations .…”
Section: Resultsmentioning
confidence: 97%
“…Despite all merits previously presented, photocatalytic water treatment, assisted by nanosized nanoparticles, shows some drawbacks that limit its practical applications. In fact, the difficulty of separation and recovery of Ag/TiO 2 nanoparticles from aqueous solutions during the photocatalytic process, in addition to the difficulty to apply on continuous flow systems pushed many researchers to immobilize silver-doped TiO 2 nanoparticles on different materials such as carbonaceous nanomaterials (Chen et al 2014;Lee et al 2015;Noreen et al 2019), magnetic materials (Tedsree et al 2017;Mehrvar 2018;Scott et al 2019), polymers, and biopolymers materials (Singh et al 2014;Rtimi et al 2015;Santhosh and Natarajan 2015;Jbeli et al 2018;Li et al 2018b;Haghighat et al 2019). This section aims to present the different supports used to overcome the problems related to the recovery of the Ag/TiO 2 nanoparticles after the photocatalysis process.…”
Section: Ag/tio 2 Ternary Nanocompositesmentioning
confidence: 99%
“…The study by Curtis et al on L. monocytogenes also concluded that MazEF is also activated under antibiotic stress and thus exhibits longā€term resilience [27]. In 2013, the study by Santosh et al demonstrated the antiā€biofilm activity of epoxy/Agā€TiO 2 polymers against E. coli and Staphylococcus strains, but the exact mechanism was not defined [28].…”
Section: Discussionmentioning
confidence: 99%